Helium in groundwaters of the Altai Republic - E. M. Dutova; V. E. Kats; A. V. Shitov; A. I. Surnin; V. A. Molokov (Геодинамика и тектонофизика, 2020)
This study of groundwaters of the Altai Republic is relevant due to the need to identify earthquake precursors in seismically active zones of the study area. Chemical composition of groundwater is widely known as an indicator of seismic processes, which changes in future earthquake focal zones. In this regard, studying helium contents in groundwater is of particular importance – anomalous concentrations of helium are typical of fault zones, and helium concentration variations in time can be referred to as earthquake precursors.Our study was focused on the distribution of helium in groundwaters of the Altai Republic and aimed to determine and justify positioning of permanent monitoring sites for investigation of earthquake precursors.During the field study, groundwater samples were taken from wells and springs located within the area covered by the established state monitoring network (GONS). Groundwater aquifers and water-bearing zones from Quaternary to Proterozoic ages were sampled.Analysis of the groundwater samples shows spatial variations of helium concentration in the study area. Water samples from fault zones have increased concentrations of helium. The concentration of helium is high in the groundwater from the Chuya artesian basin, i.e. near the epicentral zone of the M 7.5 Altai (Chuya) earthquake of September 27, 2003.